Identification and management of familial hypercholesterolaemia: what does it mean to primary care? - Qureshi, Nadeem (Royal College of General Practitioners, 2009)
Familial hypercholesterolaemia is one of the most common dominantly inherited disorders to be identified in primary care, leading to raised serum cholesterol evident from the first year of life. Around 1 in 500 people are affected by this condition, but less than 15% of these are currently attending lipid clinics, suggesting that the vast majority are unrecognised in general practice. The recently released National Institute for Health and Clinical Excellence evidence-based guideline on the identification and management of familial hypercholesterolaemia provides an opportunity to bridge this gap. Primary care has a role in systematic and opportunistic case finding, such as recognising the relevance of a family history of premature coronary heart disease and/or grossly elevated cholesterol. Although affected individuals need specialist care, GPs can reinforce the information provided by specialists and support cascade screening to other affected members of the extended family.